Fostering Critical Writers: The Impact of Integrating Deep and Transformative Learning on Undergraduates’ Scientific Writing Competence - Wuryani, Woro; Aryana, Suhud; Permana, Aditya; Nadaraning, Hasbulloh (Jurnal Pendidikan Progresif, 2025)
Fostering Critical Writers: The Impact of Integrating Deep and Transformative Learning on Undergraduates’ Scientific Writing Competence. Objectives: This research aims to examine the effectiveness of integrating Deep Learning (DL) and Transformative Learning (TL) approaches in improving students’ scientific writing competence in general Indonesian language courses. Methods: A true-experimental design with pretest and posttest control groups was used because it provides strong control, ensuring that changes in outcomes are attributable to the DL–TL treatment. The population consisted of students in elementary school teacher education at IKIP Siliwangi, and 90 were selected via cluster random sampling. The experimental group (n=45) received DL–TL integrated instruction, while the control group (n=45) received conventional instruction. The research was conducted over 16 meetings from March 4 to August 10, 2025. Data were collected using a project-based scientific writing assessment supported by rubrics evaluating content relevance and originality, organization and coherence, argumentation quality, academic language use, and citation accuracy. Observation sheets and a Likert-scale questionnaire further supported the data. Inferential analysis employed the Shapiro–Wilk test, Levene’s test, and the independent t-test, while qualitative data were analyzed using the Miles and Huberman model. Findings: the experimental group achieved significantly greater improvement (Post-test Mean = 82.11) than the control group (Post-test Mean = 73.11), with a mean difference of 9.00 points (t(88)=11.112, p<0.001). The N-Gain Score of 0.7782 and N-Gain Percent of 77.8222 indicated a high and effective category of improvement. Qualitatively, students demonstrated increased engagement, reflective disposition, and collaboration. Conclusion: DL–TL integration proved more effective than conventional learning in enhancing scientific writing and strengthening students’ critical, reflective, and collaborative capacities. Keywords: deep learning, transformative learning, scientific writing, indonesian language.